(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Hearing is an important medium, which keeps one connected to other and with the surroundings. Impairment of hearing and its severity may vary from mild to moderate or profound. It can be unilateral or bilateral and conductive or sensorineural or mixed type. Acharya Sushruta has explained 28 types of Karna-roga in Uttar Tantra an Badhriya is one of them. It is caused by Vata dosha or Kaphaavritta vata dosha by Srotorodha (obstructing of channels) of Shabdavaha srotas (pathway of hearing) and Shabdavaha sira (auditory nerve) and further ignorance of this condition leads to Badhriya. This case report presents 18 years old girl with hearing impairment in the right ear from 3 years. Audiometry reports shows moderate to severe mixed HL in right ear and left ear is normal. Treatment was done with Marsha nasyam with Shadbindu oil and Karanpooran with Bilwadi oil (right ear) for 7days. Along with Sarivadi vati, Chandraprabha vati as internal medicine for 1 month.